Prospects and contradictions of a new monetary policy of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
From the point of monetary policy the important condition of efficiency of its realization is a correct choice of the monetary accommodation model based on the certain monetary mode. The policy of the National Bank of Kazakhstan on expansion of currency corridor with the purpose of forming the floating rate of exchange and passing to inflation targeting caused the ambiguous reaction of public. On the basis of analysis of the Kazakhstan’s and countriesexporters of oil situation it would be desirable to consider the possibilities and prospects of the new monetary policy of the National Bank of Kazakhstan more in detail. In order to assess the applicability of inflation targeting it is necessary to identify the determinants of its effectiveness. By fundamentals we mean the structural features of the national economy, in which the use of inflation targeting becomes effective (t.e.macroeconomical determinants). Organizational and legal determinants are linked to two key conditions necessary for inflation targeting: the functional autonomy of the National Bank and the abandonment of targeting other variables. Accordingly, the transition to inflation targeting is necessary to solve the above problems, or to return to the old model of monetary control or transition to a new currency in a monetary union.
Keywords: monetary policy; inflation; inflation targeting; rate of exchange; the National Bank.